Survey of the improvement of fish fermentation for lanhouinproduction in Benin - DOSSOU-YOVO, PIERRE; JOSSE, Roger Gérard; Bokossa, Innocent; Palaguina, Iraïda (My University, 2011)
The objective of this study was to control ‘maturation’ process of fish during the fermentation, by using bio-organisms that can give the expected improvement. Starter culture of Lactobacillus plantarumwas used as bio-organism on species of fish such as Pseudotolithus senegalensis and Scomberomorus tritor. The inoculum was serially diluted (10 –1 to 10 –5 ) in sterile Ringer solution. The result of this improved method showed significantly a product witha mild odour compared to odour from lanhouin traditionally obtained by chance fermentation.
Keywords: Fermentation; fish; Lactobacillus plantarum; maturation; lanhouin